Boosting phosphorescence efficiency by crystal anisotropy in SrAl2O4:Eu, Dy textured ceramic layers. Issue 4 (April 2020) - Rojas-Hernandez, Rocío Estefanía; Rubio-Marcos, Fernando; Serrano, Aida; Hussainova, Irina; Fernandez, José Francisco
Graphical abstract: Abstract: Among persistent luminescence materials, one of the most studied systems is SrO-Al2 O3 due to its chemical stability and the longest green-afterglow duration. This research is focused on the synthesis of SrAl2 O4 :Eu, Dy textured layers by the screen-printing. The novelty of the approach is the employment of molten salt to promote crystal growth. The reactive ink, composed by the mixture of precursors in adequate proportions (SrCO3, Eu2 O3, Dy2 O3, and NaCl-KCl) and an organic-based vehicle, was printed onto the Al2 O3 substrates in a single step, obtaining epitaxial films. Control experiments showed that both heat treatment and substrate nature were vital ones for the improvement of the PL. Highly oriented layers demonstrated a twofold enhancement of the luminescence as compared with unoriented films. These results evidence, for the first time, that the crystal anisotropy plays a key role in the luminescence of the low symmetry structures such as the monoclinic SrAl2 O4 material. The results give the possibility of the cost-efficient production of layers by an easily scalable process.